Dietary choline, via gut microbe- generated trimethylamine-N- oxide, aggravates chronic kidney disease-induced cardiac dysfunction by inhibiting hypoxia-induced factor 1α - Xie, Feifei; Zhen, Xin; Liu, Zhuoliang; Chen, Xiaomei; Liu, Zhuanhua; Zhou, Miaomiao; Zhou, Zhanmei; Hu, Zheng; Zhu, Fengxin; Huang, Qiaobing; Zhang, Lei; Nie, Jing (Frontiers in Physiology, 2022)
Chronic kidney disease (CKD) is a global public health problem that shortens lifespan primarily by increasing the risk of cardiovascular diseases. Trimethylamine-N-oxide (TMAO), a gut microbiota-derived toxin produced by metabolizing high-choline or carnitine foods, is associated with cardiovascular events in patients with CKD. Although the deleterious effect of TMAO on CKD-induced cardiac injury has been confirmed by various researches, the mechanisms remain unclear. Here, we tested the hypothesis that TMAO aggravates CKD-induced cardiac injury and explores the potential mechanism. CD1 mice underwent sham operation or 5/6 nephrectomy to induce CKD, and CKD mice were fed with standard chow diet or the same diet supplemented with choline (1.2% total) after nephrectomy for eight weeks. Serum TMAO levels were elevated in CKD mice compared with sham group, and higher TMAO levels were found in choline-supplemented CKD mice compared with CKD group. Besides, dietary choline aggravated CKD-induced cardiac dysfunction, and reducing TMAO levels via medicinal charcoal tablets improved cardiac dysfunction. Additionally, RNA-seq analysis revealed that dietary choline affected cardiac angiogenesis in CKD mice. Reduced cardiac capillary density and expressions of angiogenesis-related genes were found in choline-treated CKD mice. Furthermore, dietary choline inhibited cardiac Hif-1α protein level in CKD mice, and Hif-1α stabilizer FG-4592 could improve cardiac angiogenesis and dysfunction in CKD mice on a high-choline diet. In conclusion, these data indicate that dietary choline, via gut microbe-generated TMAO, inhibits cardiac angiogenesis by reducing Hif-1α protein levels, ultimately aggravating cardiac dysfunction in CKD mice.